Hubungan Perilaku Masa Pubertas Remaja dengan Minat dan Motivasi Belajar IPA Biologi pada Siswa SMP Negeri 9 Kendari - Amiruddin Amiruddin; Murni Sabilu; Wa Ode Idzaa Ahkam (Universitas Negeri Makassar, 2022)
Abstract. Adolescent puberty experiences changes in behavior as a result of the work of the gonads which can directly or indirectly affect students' interest and motivation to learn. This study aims to determine the relationship between adolescent puberty behavior and interest and motivation in learning science for Biology students at SMP Negeri 9 Kendari. The population in this study were all students of SMP Negeri 9 Kendari who had experienced puberty as many as 398 people with a total sampling technique (total sampling). The data collection technique was carried out using a questionnaire by presenting a questionnaire and processed and analyzed descriptively and inferentially (chi-square test). The results showed that the behavior of puberty was obtained as many as 36 respondents (9%) had a positive category of behavior and 362 respondents (91%) behaved in a negative category. Interest in learning Science Biology obtained as many as 39 respondents (10%) have an interest in learning in the high category, 338 respondents (85%) have an interest in learning in the medium category, and 21 respondents (5%) have an interest in learning in the low category. Learning motivation for Biology Science was obtained as many as 89 respondents (22%) had a high category of learning motivation, 285 respondents (72%) had a moderate learning motivation, and 24 respondents (6%) had a low learning motivation. The results of statistical tests showed that adolescent puberty behavior was related to interest and motivation in learning Biology Science at SMP Negeri 9 Kendari (p < 0.05).Keywords: adolescent puberty behavior, interest and motivation to learn